The service quality at the Tihu Village Office, Teluk Ambon District, Ambon City - Balgis Al-Amudi; Petronela Sahetapy; Hendry Selanno (PT. Banjarese Pacific Indonesia, 2024)
This research focuses on five indicators that influence service quality at the Tihu Village Office in Teluk Ambon District, Ambon: Tangible, Reliability, Responsiveness, Assurance, and Empathy. The study aims to analyze the service quality specifically at the Tihu Village Office within Teluk Ambon Subdistrict, Ambon City. The total sample size for this study was 30 respondents, comprising 5 purposively sampled employees and 25 community respondents selected incidentally. This research adopts a quantitative approach. Data was collected using observation and questionnaires, with frequency tables used for analysis. Based on the analysis of questionnaire data across the five indicators (tangible, reliability, responsiveness, assurance, empathy), the findings indicate that the service quality at the Tihu Village Office in Teluk Ambon Subdistrict is deemed insufficient.